Manejo de las principales especies forrajeras gramíneas, para el uso en pastoreo del Ecuador - Alvario Cayo, Cesar Javier (2022)
This document deals with the management of the main gramineous forage species, for use in grazing in Ecuador. It is essential to highlight that for the development of livestock in the Ecuadorian tropics, an economically profitable exploitation system must be carried out; also delimiting that the feeding of the animals in the livestock area depends clearly on the consumption of pastures, the management and establishment of forage grass species being essential. The conclusions determined that the best gramineous forage species for use in grazing in Ecuador are Gramalote (Axonopus scoparius) since it is palatable to animals; Micay (Axonopus micay) serves as cutting grass; Janeiro (Eriocloa polystachya) provides green, tender and abundant forage; Fatty (Milinis minutiflora), is mainly for grazing, but it can be made into hay and silage; Guinea or Savoy (Panicum maximum) is susceptible to overgrazing; Elephant (Pennisetum purpureum) maintains higher nutritional values than those observed in most grasses of tropical origin; Brachiaria is resistant to trampling and Kikuyo (Pennisetum clandestinum) which is suitable for forced grazing; the pasture management system in Ecuador consists of taking advantage of the forage resource and that it is friendly to the environment, linked to this it must have a lot of dedication, time and trained labor to obtain an economically profitable production and the main thing in terms of management of pastures, is to maintain the productive levels in terms of fodder produced per hectare and per year, without the deterioration of the plant and the soil.